Price regulation and generic competition in the pharmaceutical market - Dag Morten Dalen; Steinar Strøm; Tonje Haabeth (University of Oslo, Department of Economics, 2005)
In March 2003 the Norwegian government implemented yardstick based price regulation schemes on a selection of drugs experiencing generic competition. The retail price cap, termed “index price”, on a drug (chemical substance) was set equal to the average of the three lowest producer prices on that drug, plus a fixed wholesale and retail margin. This is supposed to lower barriers of entry for generic drugs and to trigger price competition. Using monthly data over the period 1998-2004 for the 6 drugs (chemical entities) included in the index price system, we estimate a structural model enabling us to examine the impact of the reform on both demand and market power. Our results suggest that the index price helped to increase the market shares of generic drugs and succeeded in triggering price competition.
Keywords: C35; D43; I18; L11; 330; Discrete choice; demand for pharmaceuticals; monopolistic competition; evaluation of yardstick based price regulation; Pharmazeutisches Produkt; Staatliche Preispolitik; Generika; Monopolistischer Wettbewerb; Schätzung; Norwegen; Diskrete Entscheidung